WEB-BASED INTERACTIVE MULTIMEDIA FEASIBILITY AT HIGH SCHOOL LEVEL - Zahra Tazkia; Sahyar Sahyar; Rita Juliani (Universitas Negeri Medan, 2019)
The research aims to develop web-based interactive multimedia in Newton's law of motion material that meets valid, practical and effective requirements. The research method used is the development research method based on the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of the development research obtained a web-based interactive multimedia valid by media experts and media experts, very practical by users (teachers and students) and effective by small group students and limited groups. Web-based interactive multimedia can be used as a learning media for teachers and high school level students.